2020
DOI: 10.3390/app10041444
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antibacterial Influence of Two Ionic Liquids and their Corrosion Inhibition Performance

Abstract: In this paper the anti-bacterial and the anti-corrosion effect of two different ionic liquids, namely 1-(2-hydroxyethyl)-3-methylimidazolinium chloride ([OH-EMIm]Cl) and 1-ethyl-3-methyleimidazolinium chloride ([EMIm]Cl) was demonstrated. The results revealed that the corrosion inhibition influence of the ionic liquid [OH-EMIm]Cl is higher than that of the ionic liquid [EMIm]Cl. Furthermore, the ionic liquid [OH-EMIm]Cl showed better biocidal influence compared with the ionic liquid [EMIm]Cl. This indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…roughout current years, emerging approaches for shielding of metals in contradiction of decomposition have been a significant area of exploration. Generally, corrosion inhibitors are the greatest common and economic technique for monitoring the corrosion of metals against aggressive chloride media [4][5][6][7]. It has been verified that the organic compounds including atoms such as N, O, P, and S in extra exist in aromatic rings and binary or tripartite bonds.…”
Section: Introductionmentioning
confidence: 99%
“…roughout current years, emerging approaches for shielding of metals in contradiction of decomposition have been a significant area of exploration. Generally, corrosion inhibitors are the greatest common and economic technique for monitoring the corrosion of metals against aggressive chloride media [4][5][6][7]. It has been verified that the organic compounds including atoms such as N, O, P, and S in extra exist in aromatic rings and binary or tripartite bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, microorganisms tend to create biofilms on a widespread variety of metallic and non-metallic structures by using extracellular polymeric matters to entrench sessile cells [1][2][3][4][5]. The biofilms afford surroundings encouraging to the manifestation of microbial corrosion in several production sectors [6][7][8]. Microbial corrosion comprises corrosion initiated by microorganisms in addition to corrosion by another pre-existing corrosion agent that is accelerated by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly shown from these values that decreasing the weight loss values were leading to suppression of the corrosion rate and increasing the surface coverage area with increasing in inhibitor concentration and the ionic liquid compound is significantly effective against corrosion in sodium chloride solution, which suggested that the adsorption of this compound onto the wrought iron surface from chloride solutions [29][30][31][32]. Table 1: shows results of XRD analysis of corrosion products that formed on the iron surface.…”
Section: Weight Loss Measurementsmentioning
confidence: 96%